Persepsi Mahasiswa terhadap Instrumen Musik di Perpustakaan Universitas Bung Hatta dalam Kenyamanan Membaca - Putri, Aliffa Dwi; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
Abstract In this paper discussed about Student Perceptions of Musical Instruments in the Bung Hatta University Library in Reading Comfort. The purpose of this research is to describe students' perceptions of musical instruments in the Bung Hatta University Library in Padang in the comfort of reading. This research method uses a quantitative approach. Data collected by distributing questionnaires to visitors at the Bung Hatta University library. Samples taken as many as 100 respondents. The results of the questionnaire were compiled by recapitulating research results. The analysis is by describing the recapitulation results in one description to clarify the figures so that they are easy to understand. Based on the results of the study concluded as follows: 1) instrumental music playback was applied as noise to increase productivity in reading, most of the majority (78%) of respondents said they disagreed about the music in the library of Bung Hatta University, and most of the 39% of respondents stated less agree regarding Music playback can increase productivity in reading. 2) listening to music can improve concentration, most 43% of respondents said they disagree about music playback can increase concentration in reading., Most 39% of respondents said they disagree and 38% agreed that music can support reading activities. 3) listening to music can calm the mind, most 34% of respondents said that they disagree about playing music in the library making the mind calm in reading. 4) listening to music can reduce external sounds that can distract, most 41% of respondents said they disagree about playing music can reduce noise outside the library room, most of the majority of 38% of respondents said they disagree about feeling comfortable with the sound of music in the library, because listening to music can reduce external sound that distracts reading. 5) listening to music can affect the pulse and blood pressure in accordance with the frequency, tempo and volume, most 40% of respondents agree that playing music in a library with a volume that is too loud can affect heart rate and blood pressure. 6) music is an external factor that makes users feel comfortable when reading, most 41% of respondents agreed with the existence of music playback students feel comfortable in reading, most 34% of respondents said they disagree about the officers always playing music during visiting hours.Keywords: perception, musical instruments, comfort